German Grocery Discounters: Dynamics and Regional Impact. the Case of Schleswig-Holstein (Germany) - Jürgens, Ulrich (Quaestiones Geographicae, 2014)
Grocery discount stores have long dominated developments in the German food retail sector, and they continue to grow. This paper discusses the reasons for this long-term success based on internal decision-making parameters such as price, adjustment of product range, choice of location, and size of new stores. The result is significant customer acceptance, but also adverse developments viewed critically in various governance constellations. The paper is based on expert interviews and a comprehensive collection of data on grocery discount stores and supermarkets in the German federal state of Schleswig-Holstein